Law's detour : justice displaced in the Bush administration - Margulies, Peter (New York : New York University Press, 2016)
This work paints an alarming picture of the many detours that George W. Bush and his allies created to thwart transparency and undermine the rule of law after 9/11.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 1, 2016).
Keywords: Law -- Political aspects -- United States; Executive power -- United States; Judicial independence -- United States; United States -- Politics and government -- 2001-2009.; History; United States of America, USA; History of the Americas; Political science & theory; Jurisprudence & general issues; Public international law: human rights